A Central Role for Troponin C Amino-Terminal α-Helix in Vertebrate Thin Filament Ca2+-Activation - Yun Shi; Lauren A. Blackwell; Ryan K. Schroy; B. Max Cleland; Cristina M. Risi; Michelle S. Parvatiyar; Jose R. Pinto; Vitold E. Galkin; P. Bryant Chase (Physchem, 2025)
Troponin C (TnC) is the Ca2+-sensing subunit of troponin that is responsible for activating thin filaments in striated muscle, and, in turn, for regulating the systolic and diastolic contractile function of cardiac muscle. The secondary structure of vertebrate TnC is mainly composed of α-helices, with nine helices named sequentially, starting from the amino terminus, from N to A–H. The N-helix is a 12-residue-long α-helix located at the extreme amino terminus of the protein and is the only helical structure that does not participate in forming Ca2+-binding EF-hands. Evolutionarily, the N-helix is found only in TnC from mammalian species and most other vertebrates and is not present in other Ca2+-binding protein members of the calmodulin (CaM) family. Furthermore, the primary sequence of the N-helix differs between the genetic isoforms of the fast skeletal TnC (sTnC) and cardiac/slow skeletal TnC (cTnC). The 3D location of the N-helix within the troponin complex is also distinct between skeletal and cardiac troponin. Physical chemistry and biophysical studies centered on the sTnC N-helix demonstrate that it is crucial to the thermal stability and Ca2+ sensitivity of thin filament-regulated MgATPase activity in solution and to isometric force generation in the sarcomere. Comparable studies on the cTnC N-helix have not yet been performed despite the identification of cardiomyopathy-associated genetic variants that affect the residues of cTnC’s N-helix. Here, we review the current status of the research on TnC’s N-helix and establish future directions to elucidate its functional significance.